Negative electrode active material layer and alkaline storage battery
By using poorly soluble additives like Mg, Sr, and La in the negative electrode active material layer, the cycle stability of Zn-based alkaline storage batteries is enhanced by preventing ZnO localization and maintaining electrode structure integrity.
Patent Information
- Application Number
- JP2021158977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-09-29
Smart Images

Figure 0007600946000004 
Figure 0007600946000005 
Figure 0007600946000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode active material layer and an alkaline storage battery. [Background technology]
[0002] Zn-based active materials are known as negative electrode active materials for alkaline storage batteries. For example, Patent Document 1 discloses a gelled negative electrode composition for alkaline batteries containing at least zinc alloy powder, a gelling agent, and an alkaline aqueous solution. Patent Document 1 also discloses that magnesium hydroxide powder is contained in an amount of 0.01 to 0.2 wt% relative to the zinc alloy powder. Patent Document 2 also discloses an alkaline secondary electrochemical generator having a zinc cathode. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4914983 [Patent Document 2] JP 2013-016506 A Summary of the Invention [Problem to be solved by the invention]
[0004] Zn-based active materials have less environmental impact and are advantageous in terms of cost, compared to active materials containing rare earth elements (e.g., hydrogen storage alloys used in Ni-MH batteries). On the other hand, when Zn-based active materials are used, cycle characteristics tend to be poor. The present disclosure has been made in view of the above circumstances, and has as its main object to provide a negative electrode active material layer having good cycle characteristics. [Means for solving the problem]
[0005] The present disclosure provides a negative electrode active material layer for use in an alkaline storage battery, the negative electrode active material layer containing a Zn-based active material and an additive, the additive containing at least one of Mg, Sr and La, the additive having a solubility (25°C) in a 6 M aqueous potassium hydroxide solution of 120 mg / L or less, and a ratio of the additive to the Zn-based active material of 1 wt% or more and 60 wt% or less.
[0006] According to the present disclosure, the negative electrode active material layer contains a predetermined additive in a predetermined ratio, and therefore has good cycle characteristics.
[0007] In the above disclosure, the additive may be a hydroxide, oxide, fluoride, phosphate, pyrophosphate or titanate.
[0008] In the above disclosure, the additive may be a hydroxide containing Mg.
[0009] In the above disclosure, the additive may be an oxide, fluoride, phosphate, pyrophosphate or titanate containing Mg.
[0010] In the above disclosure, the additive may be a fluoride containing at least one of Sr and La.
[0011] In the above disclosure, the ratio of the additive to the Zn-based active material may be greater than 35% by weight and less than or equal to 60% by weight.
[0012] In the above disclosure, the negative electrode active material layer may contain, as the Zn-based active material, at least one of Zn simple substance, a Zn alloy, a Zn oxide, and a Zn hydroxide.
[0013] The present disclosure also provides an alkaline storage battery having a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, wherein the negative electrode active material layer is the negative electrode active material layer described above.
[0014] According to the present disclosure, by using the above-mentioned negative electrode active material layer, an alkaline storage battery having good cycle characteristics can be obtained. Effect of the Invention
[0015] The negative electrode active material layer according to the present disclosure has an effect of having good cycle characteristics. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an alkaline storage battery according to the present disclosure. [Diagram 2] 1 shows the results of evaluation of cycle stability for the evaluation batteries obtained in Examples 1 to 5 and Comparative Example 1. [Diagram 3] 1 shows the results of evaluation of cycle stability for the evaluation batteries obtained in Examples 6 to 10 and Comparative Example 1. [Figure 4] 1 shows the results of evaluating the cycle stability of the evaluation batteries obtained in Examples 10 to 12 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The negative electrode active material layer and the alkaline storage battery will be described in detail below.
[0018] A. Negative electrode active material layer The negative electrode active material layer in the present disclosure is used in an alkaline storage battery and contains a Zn-based active material and an additive. The additive contains at least one of Mg, Sr, and La. The additive has a solubility (25°C) of 120 mg / L or less in a 6M aqueous potassium hydroxide solution. The ratio of the additive to the Zn-based active material is usually 1% by weight or more and 60% by weight or less.
[0019] According to the present disclosure, the negative electrode active material layer contains a predetermined additive at a predetermined ratio, and thus has good cycle characteristics. As described above, the Zn-based active material has a smaller environmental impact and is more cost-effective than active materials containing rare earth elements (e.g., hydrogen storage alloys used in Ni-MH batteries). On the other hand, when the Zn-based active material is used, the cycle characteristics tend to be poor. One of the reasons for the poor cycle characteristics is a phenomenon called ZnO shape change.
[0020] The shape change of ZnO is a phenomenon in which the dissolution of ZnO becomes localized, resulting in a decrease in the utilization rate of the active material. The shape change of ZnO is explained using a chemical reaction formula. As shown in the following formula (1), the electrolytic deposition and dissolution reaction of metallic zinc occurs on the negative electrode during charging and discharging. Zn+2OH - ⇔ ZnO+H2O+2e - Formula (1)
[0021] Strictly speaking, formula (1) is composed of the following formulas (2) and (3). Formulas (2) and (3) are the Zn(OH)4 2- This shows a reaction mechanism in which the concentration of ZnO is maintained by the dissolution-precipitation reaction of ZnO. Zn+4OH - ⇔ Zn(OH)4 2- +2e - Formula (2) Zn(OH)4 2- ⇔ ZnO+H2O+2OH - Formula (3)
[0022] Zn(OH)4 2- The solubility of Zn(OH)4 in the electrolyte is responsive to the electrolyte environment (e.g., solute concentration, electrolyte temperature). The electrolyte environment becomes non-uniform in the battery during charge / discharge reactions. 2- The concentration of Zn(OH)4 also becomes non-uniform. 2- ZnO precipitates preferentially where the concentration of Zn is high, resulting in a shape change of ZnO (the shape of ZnO changes when it is produced from Zn).
[0023] In contrast, in the present disclosure, the cycle characteristics are improved by using an additive that contains at least one of Mg, Sr, and La and is poorly soluble in the electrolyte (alkaline solution). The reason for this is presumably that the additive that is poorly soluble in the electrolyte functions as a pillar, suppressing the localization of the dissolution of ZnO. Furthermore, the additive contains at least one of Mg, Sr, and La, and these elements and Zn(OH)4 2- It is presumed that this is because the high affinity with ZnO suppresses the localization of the dissolution solvent of ZnO. Note that the term "slightly soluble" in the present disclosure is a concept that includes "insolubility."
[0024] Also, in
[0064] of Patent Document 2, it is described that "It is also advantageous to add an alkaline earth hydroxide, such as calcium hydroxide Ca(OH)2, to the active material in a ratio of about 5 to 35% by weight relative to ZnO in order to reduce the solubility of the zincate." In general, alkaline earth metals refer to elements belonging to the second group of the periodic table and elements in the fourth or later period. Specifically, alkaline earth metals refer to the four elements Ca, Sr, Ba, and Ra. On the other hand, in the examples described below, Mg(OH)2 is used as an additive. Although Mg corresponds to an element belonging to the second group of the periodic table, it is not usually classified as an alkaline earth metal. This is because Mg (and Be) have a small atomic radius, have covalent bonding properties, and have chemical properties that are significantly different from alkaline earth metals. For reference, the solubility in pure water of Ca(OH)2 is 1700 mg / L, while that of Mg(OH)2 is 12 mg / L.
[0025] The negative electrode active material layer in the present disclosure contains a Zn-based active material and an additive, and may further contain a conductive material and a binder.
[0026] (1) Additives The additive in the present disclosure includes at least one of Mg, Sr, and La. The additive is poorly soluble in an electrolyte (alkaline solution). In the present disclosure, the solubility (25°C) in a 6M potassium hydroxide aqueous solution is used as an index of poor solubility. Specifically, when the solubility is 120mg / L or less, it can be determined that the additive is poorly soluble in an electrolyte. When the solubility is 120mg / L or less, it is equivalent to the amount of solvent required to dissolve 1.2g of solute being 10000mL (10L) or more. The solubility may be 100mg / L or less, 50mg / L or less, 25mg / L or less, 10mg / L or less, or 1mg / L or less. The solubility can be determined by adding the additive to a 6M potassium hydroxide aqueous solution, leaving it at 25°C overnight, and measuring the amount of the additive dissolved in the aqueous solution using an inductively coupled plasma (ICP) emission spectrometer.
[0027] The additive may contain at least Mg. In this case, the additive may contain only Mg as a cationic component, or may contain Mg as a main component and further contain other metal elements. In the present disclosure, the term "main component" refers to the component having the largest molar ratio.
[0028] The additive may contain at least Sr. In this case, the additive may contain only Sr as a cationic component, or may contain Sr as a main component and further contain other metal elements. The additive may contain at least La. In this case, the additive may contain only La as a cationic component, or may contain La as a main component and further contain other metal elements.
[0029] The additive is preferably a hydroxide, an oxide, a fluoride, a pyrophosphate, a titanate or a phosphate. A hydroxide is a compound that contains hydroxide ions (OH - ) as the main anion component. Oxides are compounds that contain oxygen ions (O 2-Fluoride is a compound that contains the fluoride ion (F - ) as the main anion component. Phosphate is a compound that contains the phosphate ion (PO4 3- ) as the main anion component. Pyrophosphate is a compound that contains the pyrophosphate ion (P2O7 4- ) as the main anion component. Titanates are compounds that contain the titanate ion (TiO3 4- ) as the main anion component.
[0030] In addition, fluorides often have low solubility. For reference, the solubility in pure water of MgF2 is 87 mg / L, and that of SrF2 is 117 mg / L.
[0031] Specific examples of the additive include Mg(OH)2, Mg2P2O7, Mg2TiO3, Mg3(PO4)2, MgO, MgF2, SrF2, and LaF3. The negative electrode active material layer may contain only one type of additive, or may contain two or more types of additives.
[0032] The shape of the additive can be, for example, particulate. The average particle size of the additive (D 50 ) is, for example, 1 μm or more and 300 μm or less. 50 ) is the so-called median diameter, and can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).
[0033] In the negative electrode active material layer, the ratio of the additive to the Zn-based active material is usually 1% by weight or more, may be 5% by weight or more, or may be 10% by weight or more. If the ratio of the additive is too small, the cycle characteristics may not be sufficiently improved. On the other hand, the ratio of the additive to the Zn-based active material is usually 60% by weight or less. If the ratio of the additive is too large, the ratio of the Zn-based active material may be relatively small, and the volumetric energy density may decrease. In addition, the ratio of the additive to the Zn-based active material may be, for example, greater than 35% by weight, may be 37% by weight or more, or may be 40% by weight or more.
[0034] (2)Zn-based active material The Zn-based active material contains zinc (Zn). Examples of the Zn-based active material include simple Zn, Zn alloys, Zn oxides, and Zn hydroxides. The Zn alloy is preferably an alloy containing Zn as a main component. The ratio of Zn in the Zn alloy is, for example, 50 atm% or more, may be 70 atm% or more, or may be 90 atm% or more. The Zn alloy may further contain, for example, at least one of In, Al, Bi, Mg, and Ca. Examples of the Zn oxide include ZnO. Examples of the Zn hydroxide include Zn(OH)2. The negative electrode active material layer may contain only one type of Zn-based active material, or may contain two or more types.
[0035] The shape of the Zn-based active material may be, for example, particulate. 50 ) is, for example, 1 μm or more and 300 μm or less. The ratio of the Zn-based active material in the negative electrode active material layer is, for example, 50% by weight or more, and may be 70% by weight or more. On the other hand, the ratio of the Zn-based active material in the negative electrode active material layer is, for example, less than 100% by weight.
[0036] (3) Negative electrode active material layer The negative electrode active material layer may further contain at least one of a conductive material and a binder. By using a conductive material, the electronic conductivity of the negative electrode active material layer is improved. Examples of the conductive material include metal powders such as Ni powder; oxides such as cobalt oxide; and carbon materials such as graphite and carbon nanotubes. Examples of the binder include rubber-based binders such as styrene butadiene rubber; cellulose-based binders such as carboxymethyl cellulose (CMC); and fluororesin-based binders such as polyvinylidene fluoride (PVDF). The negative electrode active material layer in the present disclosure is usually used in alkaline storage batteries.
[0037] B. Alkaline storage battery Fig. 1 is a schematic cross-sectional view illustrating an alkaline storage battery according to the present disclosure. The alkaline storage battery 10 shown in Fig. 1 has a positive electrode active material layer 1 containing Ni(OH)2 as a positive electrode active material, the above-mentioned negative electrode active material layer 2, and an electrolyte layer 3 formed between the positive electrode active material layer 1 and the negative electrode active material layer 2 and containing an electrolyte solution (alkaline solution). The alkaline storage battery 10 shown in Fig. 1 corresponds to a so-called nickel-zinc battery (Ni-Zn battery), in which the following reaction occurs: Positive electrode: NiOOH+H2O+e - ⇔ Ni(OH)2+OH - Negative electrode: Zn+2OH - ⇔ ZnO+H2O+2e -
[0038] In addition, oxygen (O2) may be used as the positive electrode active material instead of Ni(OH)2. For example, oxygen is supplied from the atmosphere during discharge and released into the atmosphere during charge. Such an alkaline ion battery corresponds to an air-zinc battery (Air-Zn), and the following reaction occurs: Positive electrode: O2+2H2O+4e - ⇔ 4OH - Negative electrode: Zn+2OH - ⇔ ZnO+H2O+2e -
[0039] According to the present disclosure, by using the above-mentioned negative electrode active material layer, an alkaline storage battery having good cycle characteristics can be obtained.
[0040] 1.Negative electrode active material layer The negative electrode active material layer in the present disclosure is the same as that described above in "A. Negative electrode active material layer", and therefore the description thereof will be omitted here. In an alkaline storage battery, the additive contained in the negative electrode active material layer is usually present as a solid.
[0041] 2.Cathode active material layer The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer may further contain at least one of a conductive material and a binder. Examples of the positive electrode active material include a metal element, an alloy, and a hydroxide. In particular, the positive electrode active material preferably contains Ni element, and more preferably nickel hydroxide. The conductive material and the binder are the same as those described in "A. Negative electrode active material layer". In addition, when the positive electrode active material of the positive electrode active material layer is air, it is preferable to contain a catalyst that promotes the electrode reaction. Examples of the catalyst include a precious metal such as Pt, and a composite oxide such as a perovskite-type oxide.
[0042] 3. Electrolyte layer The electrolyte layer is formed between the positive electrode active material layer and the negative electrode active material layer, and contains an alkaline solution as an electrolyte. Examples of the solute of the alkaline solution include metal hydroxides such as potassium hydroxide (KOH) and sodium hydroxide (NaOH). Examples of the solvent of the alkaline solution include water. The ratio of water to the entire solvent of the electrolyte is, for example, 50 mol% or more, may be 70 mol% or more, or may be 90 mol% or more. The concentration of the solute in the alkaline solution is, for example, 3 mol / L or more, may be 5 mol / L or more. On the other hand, the concentration of the solute in the alkaline solution is, for example, 8 mol / L or less. A separator may be disposed between the positive electrode active material layer and the negative electrode active material layer, and the separator may be impregnated with the alkaline solution. A known separator can be used as the separator.
[0043] 4. Alkaline storage batteries The alkaline storage battery in the present disclosure contains at least the above-mentioned negative electrode active material layer, positive electrode active material layer, and electrolyte layer. The alkaline storage battery may have a positive electrode current collector that collects electrons from the positive electrode active material layer. Examples of the material for the positive electrode current collector include stainless steel, nickel, iron, titanium, and the like. Examples of the shape of the positive electrode current collector include foil, mesh, and porous. The alkaline storage battery may also have a negative electrode current collector that collects electrons from the negative electrode active material layer. Examples of the material for the negative electrode current collector include copper, stainless steel, nickel, iron, titanium, and carbon. Examples of the shape of the negative electrode current collector include foil, mesh, and porous. In addition, a known exterior body can be used as the exterior body of the alkaline storage battery.
[0044] The alkaline storage battery in the present disclosure is preferably a secondary battery. The applications of the alkaline storage battery are not particularly limited, but include, for example, a power source for vehicles such as hybrid electric vehicles (HEVs).
[0045] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0046] [Comparative Example 1] (Preparation of electrolyte) A potassium hydroxide (KOH) aqueous solution with a concentration of 4M (mol / L) and a potassium hydroxide (KOH) aqueous solution with a concentration of 8M (mol / L) were mixed to prepare a potassium hydroxide (KOH) aqueous solution with a concentration of 6M (mol / L). Then, zinc oxide (ZnO) was added to the obtained aqueous solution until a precipitate remained. Then, the solution was left to stand overnight in a thermostatic bath at 25°C. As a result, an electrolyte solution containing potassium hydroxide (KOH) with a concentration of 6M (mol / L) and ZnO at a saturated concentration was obtained.
[0047] (Preparation of separator) A polypropylene separator (PP separator, 20μm×58mm×70mm) was prepared and subjected to hydrophilic treatment. Specifically, 1g of a fluorosurfactant was added to a solution obtained by mixing 50g of ethanol and 50g of ultrapure water, and the solution was stirred. The PP separator was immersed in the stirred solution for 1 minute, and then naturally dried. This resulted in a hydrophilic PP separator. The hydrophilic PP separator was then placed on both sides of a nonwoven PP separator, and a separator was obtained.
[0048] (Preparation of positive electrode) The positive electrode active material (nickel hydroxide, Ni(OH)2), conductive material (cobalt oxide, CoO), first binder (styrene butadiene rubber, SBR), and second binder (carboxymethyl cellulose, CMC) were weighed out so that the weight ratio was Ni(OH)2:CoO:SBR:CMC=87:10:2.5:0.5, and kneaded in a mortar. Then, ultrapure water was added, and the mixture was mixed at 2000 rpm for 1 minute using a rotation-revolution mixer (Thinky Mixer), to obtain an ink. The obtained ink was applied to the surface of a positive electrode current collector (Ni foil) with a doctor blade. After natural drying, the mixture was dried overnight in a reduced pressure environment at 80°C. This resulted in a positive electrode having a positive electrode current collector and a positive electrode active material layer.
[0049] (Preparation of negative electrode) The first negative electrode active material (zinc oxide, ZnO), the second negative electrode active material (zinc, Zn), the first binder (styrene butadiene rubber, SBR), and the second binder (carboxymethyl cellulose, CMC) were weighed out so that the weight ratio was ZnO:Zn:SBR:CMC=77:20:2.5:0.5, and kneaded in a mortar. Then, ultrapure water was added, and the mixture was mixed at 2000 rpm for 1 minute using a rotation-revolution mixer (Thinky Mixer), to obtain an ink. The obtained ink was applied to the surface of a negative electrode current collector (Cu foil plated with Sn) using a doctor blade. After natural drying, the mixture was dried overnight in a reduced pressure environment at 80°C. This resulted in a negative electrode having a negative electrode current collector and a negative electrode active material layer.
[0050] (Preparation of evaluation battery) The obtained positive electrode, negative electrode, separator and electrolyte were placed in a resin two-electrode cell (SB8, manufactured by EC Frontier) to obtain a battery for evaluation.
[0051] [Example 1] When preparing the negative electrode, Mg(OH)2 was used as the additive, and the weight ratio of the additive was changed to 1 wt% relative to the Zn-based active material (ZnO+Zn) (specifically, the ratio of Zn in the negative electrode active material layer was fixed at 10 wt%, and the ratio of ZnO was reduced to adjust the ratio). Except for this, a battery for evaluation was obtained in the same manner as in Comparative Example 1.
[0052] [Examples 2 to 5] Evaluation batteries were obtained in the same manner as in Example 1, except that the weight ratio of the additive was changed to 10 wt %, 20 wt %, 40 wt %, and 60 wt % relative to the Zn-based active material (ZnO+Zn).
[0053] [evaluation] Charge and discharge measurements were performed to evaluate cycle stability using the evaluation batteries obtained in Examples 1 to 5 and Comparative Example 1. An electrochemical measurement system (VMP3, Biologic) and a thermostatic bath (SU-642, Espec) were used for the charge and discharge measurements. The charge and discharge conditions were as follows: Charge / discharge range: SOC 0% to 100% (theoretical capacity of the positive electrode is 100%) Charge / discharge current: 3.5mA / cm 2 Cutoff voltage: Charge 2V, Discharge 1.3V Rest: 5 minutes
[0054] In the charge-discharge measurement, the initial discharge capacity was set as 100%, and the number of cycles until the discharge capacity decreased to 70% was measured. The number of cycles was also normalized by dividing it by the capacity ratio (negative electrode capacity / positive electrode capacity). The results are shown in Table 1 and Figure 2.
[0055] [Table 1]
[0056] As shown in Table 1 and FIG. 2, Examples 1 to 5 had better cycle stability than Comparative Example 1.
[0057] [Examples 6 to 10] Batteries were obtained in the same manner as in Example 3, except that Mg2P2O7, Mg2TiO3, Mg3(PO4)4, MgO, and MgF2 were used as the additives.
[0058] [evaluation] Charge / discharge measurements were carried out using the evaluation batteries obtained in Examples 6 to 10, and cycle stability was evaluated in the same manner as described above. The results are shown in Table 2 and FIG.
[0059] [Table 2]
[0060] 3, Examples 6 to 10 had better cycle stability than Comparative Example 1. Moreover, from the results of Examples 6 to 10 and Example 1, it was confirmed that good cycle stability was obtained in various additive materials containing Mg.
[0061] [Examples 11 and 12] Evaluation batteries were obtained in the same manner as in Example 3, except that SrF2 and LaF3 were used as the additives.
[0062] [Comparative Examples 2 and 3] Evaluation batteries were obtained in the same manner as in Example 3, except that NiF2 and CaF2 were used as the additives.
[0063] [evaluation] Charge / discharge measurements were carried out using the evaluation batteries obtained in Examples 11 and 12 and Comparative Examples 2 and 3, and cycle stability was evaluated in the same manner as described above. The results are shown in Table 3 and FIG.
[0064] [Table 3]
[0065] As shown in Table 3 and Fig. 4, Examples 11 and 12 had better cycle stability than Comparative Example 1. In addition, from the results of Examples 11 and 12 and Example 10, good cycle stability was obtained with SrF2 and LaF3, which are fluorides other than MgF2. On the other hand, as in Comparative Examples 2 and 3, good cycle stability was not obtained with NiF2 and LaF3.
[0066] [Reference example] Mg(OH)2 was added to a 6M (mol / L) aqueous solution of potassium hydroxide (KOH) and left to stand overnight in a thermostatic bath at 25°C. The concentration of Mg(OH)2 dissolved in the solution was then measured using an inductively coupled plasma (ICP) optical emission spectrometer, which revealed that it was below the detection limit (0.01mg / L), confirming that Mg(OH)2 is poorly soluble in the KOH aqueous solution. [Explanation of symbols]
[0067] 1... Positive electrode active material layer 2 … Negative electrode active material layer 3 … Electrolyte layer 10. Alkaline storage battery
Claims
1. A negative electrode active material layer for use in an alkaline storage battery, The negative electrode active material layer contains a Zn-based active material and an additive, The additive material contains at least one of Mg, Sr, and La, The additive has a solubility (25° C.) of 120 mg / L or less in a 6 M potassium hydroxide aqueous solution; the additive is a hydroxide, an oxide, a fluoride, a phosphate, a pyrophosphate, or a titanate; The negative electrode active material layer comprises a Zn-based active material having a ratio of the additive to the Zn-based active material of 20% by weight or more and 40% by weight or less.
2. The negative electrode active material layer as described in claim 1, wherein the additive includes at least one of Mg(OH)2, Mg2P2O7, Mg2TiO3, Mg3(PO4)2, MgO, MgF2, SrF2 and LaF3.
3. The negative electrode active material layer according to claim 1, wherein the additive contains at least Mg 2 P 2 O 7 .
4. The negative electrode active material layer according to claim 1, wherein the additive comprises at least Mg 2 TiO 3 .
5. The negative electrode active material layer according to claim 1, wherein the additive material at least contains LaF 3 .
6. The negative electrode active material layer according to claim 1 , wherein the negative electrode active material layer contains, as the Zn-based active material, at least one of a Zn element, a Zn alloy, a Zn oxide, and a Zn hydroxide.
7. An alkaline storage battery having a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, An alkaline storage battery, wherein the negative electrode active material layer is the negative electrode active material layer according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP1974014983A
JP1974119127A
Alkaline zinc storage battery
JP1987064061A
Zinc secondary battery and zinc electrode
JP1996069793A
Secondary electrochemical generators of zinc-anode alkaline type
JP2013016506A
